(untitled) (Bangladesh Journal of Medical Microbiology, 2019)
Background: Clarithromycin and Levofloxacin are most frequently included in the standard triple therapies for H. pylori eradication in our country. Resistance to clarithromycin and fluoroquinolones are particularly related with treatment failure. Objectives: The objective of this study was to detect, clarithromycin and levofloxacin resistance associated with gene mutations in H. pylori directly from gastric biopsies using an allele specific primer-PCR (ASP-PCR) assay. Materials and Methods: Gastric biopsy specimens were collected from 143 adult dyspeptic patients, from Department of Gastroenterology, BSMMU and Dhaka Medical College Hospital (DMCH), during the period of March, 2018 to February, 2019. H. pylori was identified by rapid urease test, ureC gene by PCR, histological staining and culture. ASP-PCR was used to identify 23S rRNA gene and gyrA gene mutation predictive of clarithromycin and levofloxacin resistant H. pylori respectively. Results: H. pylori positive cases were 32.9% based on the case definition used in the study. Among 42 ureC positive H. pylori cases, point mutations in 23Sr RNA gene for clarithromycin resistance were detected only at A2142G position in 9 (21.4%) cases and gyrA gene mutations for levofloxacin resistance were detected in 16 (38.1%) cases. Only 1 (2.4%) case had mutation both in 23Sr RNA and gyrA gene. Conclusion: Those findings may guide toward the therapeutic choices in our country. PCR based diagnostic assays can be the alternative approach for rapid detection of antibiotic resistances of H. pylori directly from gastric biopsies, where culture and susceptibility tests are not routinely performed. Bangladesh J Med Microbiol 2019; 13 (1): 12-19